The effectiveness of using video on students’ speaking ability - Zulfiah Rohmah; Zanuba Arifah Khofshoh (PPPM STKIP PGRI Lamongan, 2021)
In learning English, speaking is one of the most important skills for students. Especially for students who still have strong feelings, these students will have difficulty learning to speak English.Talking is about putting ideas into words about perceptions, feelings and intentions to make others catch the message conveyed. From the results of the paired sample t test analysis shows that sig. the value is 0.000. Lower than the significance level (α) = 0.05 with degrees of freedom (df) = N-1 and the number of subjects (N) is 20 students. According to the value of sig. (2-tails) is 0.000. Given the basic concept of testing the hypothesis that if sig. (2-tailed) is smaller than (α) = 0.05, meaning that the hypothesis (H1) is accepted while the null hypothesis (H0) is rejected. Thus, it can be concluded that there is a significant effect of video media on the speaking skills of class XII students of MA Al-ihsan Deket Lamongan